Advances in Power Electronics and Instrumentation Engineering Second International Conference, PEIE 2011, Nagpur, Maharashtra, India, April 21-22, 2011. Proceedings - Das, Vinu V.; Thankachan, Nessy; Debnath, Narayan C. (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the Second International Conference on Advances in Power Electronics and Instrumentation Engineering, PEIE 2011, held at Nagpur, India, in April 2011. The 9 revised full papers presented together with 4 short papers and 7 poster papers were carefully reviewed and selected from numerous submissions. The papers address current issues in the field of power electronics, communication engineering, instrumentation engineering, digital electronics, electrical power engineering, electrical machines, information technology, control systems, and the like.